Metabolic Risks Are Increasing in Non-B Non-C Early-Stage Hepatocellular Carcinoma: A 10-Year Follow-Up Study - Lin, Yen-Po; Wang, Pei-Ming; Chuang, Ching-Hui; Yong, Chee-Chen; Liu, Yueh-Wei; Huang, Pao-Yuan; Yao, Chih-Chien; Tsai, Ming-Chao (Frontiers in Oncology, 2022)
Background Non-B, non-C hepatocellular carcinoma (NBNC-HCC) may be related to metabolic syndrome, and the incidence of this tumor type is increasing annually. The definition of metabolic-associated fatty liver disease (MAFLD) proposed in 2020 may help to more accuratelyassess the association between metabolic syndrome and NBNC-HCC. However, this new concept has not yet been applied in NBNC-HCC research. Therefore, this study aimed to compare the clinicopathological characteristics of patients with NBNC-HCC and CHB-HCC diagnosed between 2009-13 and 2014-18, focusing on metabolic risk factors and the new concept of MAFLD. Method Patients with BCLC-0/A-HCC who received curative hepatectomy between January 2009 and December 2018 were retrospectively assessed; the associations between clinicopathological characteristics and clinical outcomes of NBNC-HCC and CHB-HCC were analyzed by multivariate analysis. Result Compared to patients diagnosed in 2009-13, the frequency of metabolic disorders in NBNC-HCC was significantly higher in 2014-18 [DM (p=0.049), HTN (p=0.004), BMI (p=0.017) and MAFLD (p=0.003)]; there was no significant change in patients with CHB-HCC. Moreover, CHB-HCC was an independent risk factor for HCC recurrence (HR, 1.339; 95% CI, 1.010-1.775, p=0.043) and death (HR, 1.700; 95% CI, 1.017-2.842, p=0.043) compared to NBNC-HCC. Conclusions Therisk of MAFLD, obesity, DM, and hypertension in patients with early-stage NBNC have significantly increased in recent years, thus metabolic syndrome should be monitored in this special population. Moreover, NBNC-HCC tend to had a better prognosis than CHB-HCC, probably due to their distinct clinicopathological features.